La grippe la plus meurtrière - Spinney, Laura (Comptes Rendus Biologies, 2023)
Many questions remain unanswered regarding the so-called “Spanish” influenza pandemic of 1918. This article addresses three of them and describes the state of knowledge for each of them: Where did the pandemic start? How many people died? And why was it so deadly?